(3ebGQHI GdcaGAGJ GdeMhQjI (B:s (3GdEJLGg GdeYGUQ ddejRI GdJfGaSjI HefXeGJ GdCYeGd (B/s - (3YUfjf, SGejI s ((3GdLRGFQ (B: s (3OGQ CLjGd GdQbej (B, s, 2024)
(3jYGdL gPG GdcJGH YQV ehLR dJWhQ GdacQ GdESJQGJjLj, MjK Je GdJQcjR ajg Ydi ebGQHI GdcaGAGJ GdeMhQjI cCMO Cge eOGNd JMbjb GdejRI GdJfGaSjI Pdc ef NdGd GdJQcjR Ydi JMdjd GdHjFI GdOGNdjI ddefXeI GdJQcjR Ydi fbGW GdbhI Ohf EgeGd JCKjQGJ GdHjFI GdNGQLjI, hdbO GSJYQV GdcJGH eVehf ebGQHI GdehGQO ceONd dOQGSI eaghe GdcaGAGJ GdeMhQjI (B,(3ceG Je GdJWQb dSjQhQI JMOjO gPG GdfhY ef GdcaGAGJ hcPG GdNjGQGJ GdGSJQGJjLjI dJWhjQgG hJLOjOgG, haj GdCNjQ GSJYQV GdcJGH GdEWGQ GdeaGgjej ddejRI GdJfGaSjI hcjajI JMbjbgG ef NdGd GdGSJZdGd GdLjO deKd gPG GdfhY ef GdcaGAGJ(B.s
(3HjHdjhZQGajG(B: (3U U(B.134-155s
Keywords: (3EOGQI GdCYeGds; (3GdefGaSIs; (3GdehGQO GdHTQjIs